2011
DOI: 10.1080/17470218.2011.593264
|View full text |Cite
|
Sign up to set email alerts
|

Conserving Time in the Classroom: The Clicker Technique

Abstract: Any technique that conserves classroom instructional time without sacrificing the amount learned is of great educational value. This research compared a laboratory analogue of the clicker technique to analogues of other classroom pedagogical methods that all involve repeated testing during teaching. The clicker analogue mimics the classroom practice of dropping material that is understood by the majority of the class, as revealed by testing with clicker questions, from further lecture. A fact learning and retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Such issues would likely be eliminated or greatly reduced with additional training and experience using the PRDs. With experience, instructors should recognize that clickers eliminate the need to discuss topics that are well understood and allow more time to discuss topics where misunderstandings are evidenced (Anderson, Healy, Kole, & Bourne 2011). Smooth transitions back to the lecture will occur as instructors establish standard classroom protocols for PRD use.…”
Section: Discussionmentioning
confidence: 99%
“…Such issues would likely be eliminated or greatly reduced with additional training and experience using the PRDs. With experience, instructors should recognize that clickers eliminate the need to discuss topics that are well understood and allow more time to discuss topics where misunderstandings are evidenced (Anderson, Healy, Kole, & Bourne 2011). Smooth transitions back to the lecture will occur as instructors establish standard classroom protocols for PRD use.…”
Section: Discussionmentioning
confidence: 99%
“…This challenged the teachers to change their teaching based on the student response. In a lab-based study, Anderson, Healy, Kole, and Bourne (2011) found that feedback from clicker interventions also helped save teaching time since the teacher could focus on the most relevant topics for the students' current level of understanding. Kolikant, Drane, and Calkins (2010) followed and interviewed three university teachers who used SRS in their classes (in mathematics, physics and engineering).…”
Section: Previous Researchmentioning
confidence: 99%
“…Both online and clicker quizzes are generally easily implemented, although a possible disadvantage is that they may be less potent than more extensive formats (Rowland, 2014). Both methods have been investigated in the classroom in relatively few studies to date (e.g., Anderson et al, 2011;Glass, 2009;Mayer et al, 2009;McDaniel et al, 2007).…”
Section: The Present Studymentioning
confidence: 99%